EKSISTENSI BADAN PERMUSYAWARATAN DESA DALAM MENAMPUNG DAN MENYALURKAN ASPIRASI MASYARAKAT DI DESA MAHATO KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - Arif Rahman; Dessy Artina; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The Village Consultative Body is not an element of village administration. The VillageConsultative Body is only an institution that has a government function, standing aloneoutside the village government structure. The enactment of Law article 55 Number 6 of 2014., again changed the arrangements related to village government. However, in this study theMahato Village Consultative Body, Tambusai Utara District, Rokan Hulu Regency, has notbeen able to carry out the functions of the Village Consultative Body in Accommodating andDistributing the aspirations of the Mahato Village Community, this study aims to examinefurther related to the existence of the Village Consultative Body in accommodating andchannel the aspirations of the village community.This type of research is sociological juridical research which emphasizes the researchapproach to legal aspects relating to the subject matter discussed, in relation to the facts orrealities that exist at the research location. This research was conducted in Mahato Village,North Tambusai District, Rokan Hulu Regency, by conducting research in Mahato villagegovernment, Mahato Village Consultative Body, Traditional Leaders, and Mahato VillageCommunity, the data sources used are primary and secondary data, data collectiontechniques in this study were carried out by observation, questionnaires, interviews andliterature review.In the results of research problems there are main things that can be concluded. First,the existence of the village consultative body in accommodating and channeling theaspirations of the community has not been implemented properly, in accordance withapplicable regulations. Second, the Village Consultative Body has not been able tounderstand what is meant and how to accommodate and channel the aspirations of thecommunity and there is no forum or infrastructure from the village government toaccommodate and channel the aspirations of the community. The three efforts to fulfill theobligation to carry out the function as a reservoir and channel the aspirations of thecommunity are only carried out by public complaints in coffee shops. However, in fulfillingthis community's rights, the Mahato Village Consultative Body seeks to increase communityparticipation and further improve the functions and authorities of the performance of theVillage Consultative Body.Keywords: Existence – Function